1985
DOI: 10.1002/macp.1985.021860906
|View full text |Cite
|
Sign up to set email alerts
|

Functional monomers and polymers, 129. Asymmetric robinson cyclization reaction catalyzed by polymer‐bound L‐proline

Abstract: The asymmetric Robinson cyclization reaction was studied by using polymer-bound L-prolines as catalysts, in which the degree of crosslinking, the content of proline and the spacers of binding L-proline to the polymers were varied. Incorporation of a spacer for binding the L-proline moiety onto a polymer support was found to improve the catalytic efficiency considerably, which is reflected by the value of enantiomeric excess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…[85] Their behavior has already been discussed in the previous review. [4] More recent efforts involved the synthesis of prolinamide 28 ( Figure 11) obtained by condensation of proline with 4-methylbenzhydrylamino polystyrene (MBHA).…”
Section: Catalysts Derived From Amino Acidsmentioning
confidence: 93%
“…[85] Their behavior has already been discussed in the previous review. [4] More recent efforts involved the synthesis of prolinamide 28 ( Figure 11) obtained by condensation of proline with 4-methylbenzhydrylamino polystyrene (MBHA).…”
Section: Catalysts Derived From Amino Acidsmentioning
confidence: 93%
“…[27] Already in 1985, a group of Japanese researchers reported the first type of polymer-supported proline, used for this very reaction (Scheme 1). [28] Although the catalytic efficiency and selectivity by today's standards of this supported proline must be perceived as mediocre, [28] it nevertheless bears a striking resemblance to the supports that about 20 years later would give the field of polymersupported proline its breakthrough. As for most reports nowadays, the Merrifield resin and the proline derivative trans-4-hydroxy--proline was the starting point (Scheme 1).…”
Section: Polymer-supported Proline Pioneering Effortsmentioning
confidence: 96%
“…Subsequent deprotection gave polymer-supported proline 13 (Scheme 1). [28] A close derivative containing a methylene spacer was also prepared. [28] Unfortunately, the catalyst was rather ineffective in the asymmetric Robinson cyclization, but the authors used optical rotation for determination of enantiomeric excess, a procedure prone to inaccuracies as small amounts of pollutants can give highly distorted results.…”
Section: Polymer-supported Proline Pioneering Effortsmentioning
confidence: 99%
“…An explanation for the observed differences may be that Agami and colleagues (21) had used optical rotation measurement for the ee determinations, whereas we had used a more accurate HPLC-based assay. Another strong piece of evidence for our one-proline mechanism came from studies with polymer-supported proline as the catalyst for asymmetric inter-and intramolecular aldolizations and for our previously discovered asymmetric Mannich reaction (10,(27)(28)(29). It was shown that rates and enantioselectivities of the supported catalysts are comparable with proline itself.…”
mentioning
confidence: 95%